Strategic differentiation of digital marketing content in South African organisations - Van der Klooster, Theresa (My University, 2016)
In recent times, digital marketing content has evolved into an invaluable strategic tool to help organisations in their efforts to gain market share and achieve sustainable growth. Many organisations are actively investing in various forms of digital marketing content and measuring ROI. Simultaneously, this form of marketing holds a very small percentage of the entire South African marketing budget and the bulk of available content on the net is unstructured. The purpose of the study was therefore to investigate strategic differentiation of digital marketing content in South African organisations. Semi structured interviews helped the researcher to understand what is considered to be strategic digital marketing content from the viewpoint of digital marketing specialists and marketing executives of large organisations. The theories or principles used for implementation and how South African organisations are measuring their digital content marketing efforts were also investigated. The results that are presented show that strategic marketing content in South Africa is mainly perceived as the ability of organisations to accurately segment their created content to target audiences, and by means of digital analytics actively improve their digital content messages through a process of testing and adjusting their digital marketing content accordingly. Other than segmentation, other perceptions of strategic digital marketing content include a defined value proposition or purpose portrayed through digital content marketing messages, hands on management, accurately selecting digital content marketing channels and the ability to measure digital marketing efforts. A vast number of measurement tools were indicated by the interviewees including analytics, using traditional marketing terminology for measurement and new forms of measurement such as machine learning. The research question regarding digital content marketing integration highlighted an area that needs iii improvement within South Africa. Finally, the information gained through the interview and recent academic literature helped the researcher to create a proposed model to assist companies with digital content marketing implementation and the measurement thereof.
MBA
Keywords: Internet marketing -- South Africa. Marketing -- South Africa -- Management. Marketing channels -- South Africa. Strategic planning -- South Africa.